A Retrospective Study of the Clinical Burden of Hospitalized All-Cause and Pneumococcal Pneumonia in Canada. (29th March 2016) - McNeil, Shelly A.; Qizilbash, Nawab; Ye, Jian; Gray, Sharon; Zanotti, Giovanni; Munson, Samantha; Dartois, Nathalie; Laferriere, Craig
Abstract : Background . Routine vaccination against Streptococcus pneumoniae is recommended in Canada for infants, the elderly, and individuals with chronic comorbidity. National incidence and burden of all-cause and pneumococcal pneumonia in Canada (excluding Quebec) were assessed. Methods . Incidence, length of stay, and case-fatality rates of hospitalized all-cause and pneumococcal pneumonia were determined for 2004–2010 using ICD-10 discharge data from the Canadian Institutes for Health Information Discharge Abstract Database. Population-at-risk data were obtained from the Statistics Canada census. Temporal changes in pneumococcal and all-cause pneumonia rates in adults ≥65 years were analyzed by logistic regression. Results . Hospitalization for all-cause pneumonia was highest in children <5 years and in adults >70 years and declined significantly from 1766/100, 000 to 1537/100, 000 per year in individuals aged ≥65 years (P < 0.001 ). Overall hospitalization for pneumococcal pneumonia also declined from 6.40/100, 000 to 5.08/100, 000 per year. Case-fatality rates were stable (11.6% to 12.3%). Elderly individuals had longer length of stay and higher case-fatality rates than younger groups. Conclusions . All-cause and pneumococcal pneumonia hospitalization rates declined between 2004 and 2010 in Canada (excluding Quebec). Direct and indirect effects from pediatric pneumococcal immunization may partly explain some of this decline. Nevertheless, the burden of disease from pneumonia remains high.